The ex-pat effect: presence of recent Western immigrants is associated with changes in age at first birth and birth rate in a Maya population from rural Guatemala. (4th July 2017) - McKerracher, Luseadra; Collard, Mark; Altman, Rachel; Richards, Michael; Nepomnaschy, Pablo
Abstract: Background: Economic transitions expose indigenous populations to a variety of ecological and cultural challenges, especially regarding diet and stress. These kinds of challenges are predicted by evolutionary ecological theory to have fitness consequences (differential reproduction) and, indeed, are often associated with changes in fertility dynamics. It is currently unclear whether international immigration might impact the nature of such an economic transition or its consequences for fertility. Aim: To examine measures of fertility, diet and stress in two economically transitioning Maya villages in Guatemala that have been differentially exposed to immigration by Westerners. Subjects and methods: This study compared Maya women's ages at first birth and birth rates between villages and investigated whether these fertility indicators changed through time. It also explored whether the villages differed in relation to diet and/or a proxy of stress. Results: It was found that, in the village directly impacted by immigration, first births occurred earlier, but birth rate was slower. In both villages, over the sampled time window, age at first birth increased, while birth rate decreased. The villages do not differ significantly in dietary indicators, but the immigration-affected village scored higher on the stress proxy. Conclusion: Immigration can affect fertility in host communities. This relationship between immigration and fertility dynamics may be partly attributable to stress, but this possibility should be evaluated prospectively in future research.